COPING STRATEGY PASIEN SKIZOFRENIA DI LAYANAN REHABILITASI WISMA LARAS ASRI RUMAH SAKIT JIWA PROF. DR. SOEROJO MAGELANG - Dea Raekinsa Marselyona; Moch. Zaenal Hakim, Ph.D; Dr. Uke Hani Rasalwati, M.Si (Politeknik Kesejahteraan Sosial Bandung, 2021)
Patients with schizophrenia who have been declared recovered may relapse is accompanied by symptoms such as hallucinations or delusions. There are several factors that cause relapse in schizophrenic patients such as conflicts with family, surrounding communities, or work that can cause stress. With the problems and psychosocial conditions of the patient, coping or self-defense is needed to avoid the risk of recurrence and not cause new problems or losses for yourself and those around you. This study aims to explore the coping strategy in schizophrenia patients who follow the rehabilitation service of Wisma Laras Asri at Prof. Dr. Soerojo Hospital Magelang. Aspects of coping strategy by Lazarus and Folkman is divided into two: the problem focused coping and emotional focused coping. This research uses descriptive qualitative methods, data collection uses purposive sampling, and to to collect data using techniques including: interview, observation, and documentation. The results of this study indicate that schizophrenic patients tend to use emotional focused coping in dealing with problems or pressures that befall them. The lack of skills and abilities of patients with schizophrenia in problem solving is one factor aspects of emotional focused coping more frequently used.